World, chase me down [large type] : a novel - Hilleman, Andrew, 1982- (Thorndike Press, 2017)
"Once the most wanted man in America, Pat Crowe is a forgotten folk hero who captivated the nation as an outlaw for economic justice. World, Chase Me Down resurrects him, telling the electrifying story of the first great crime of the last century: how in 1900 the out-of-work former butcher kidnapped the teenage son of Omaha's wealthiest meatpacking tycoon for a ransom of $25,000 in gold, and then burgled, safe-cracked, and bond-jumped his way across the country and beyond, inciting a manhunt that was dubbed "the thrill of the nation" and a showdown in the court of public opinion between the haves and have-nots--all the while plotting a return to the woman he never stopped loving."--